Macroeconomic determinants of housing affordability in the European Union: panel evidence from the house price-to-income ratio - Snieška, Vytautas; Burkšaitienė, Daiva (Transformations In Business & Economics, 2026)
Housing affordability has become an increasingly important socio-economic issue across the European Union as housing prices have grown faster than household incomes in many countries. This study investigates the macroeconomic determinants of housing affordability using the house price-to-income ratio as the main indicator. The empirical analysis is based on panel data for EU member states covering the period 2000–2024 and combines macroeconomic indicators from Eurostat, including GDP per capita, purchasing power parity indicators and GDP price level indices. Panel econometric models with country and time fixed effects are used to estimate the relationship between macroeconomic variables and housing affordability dynamics. In addition, cluster analysis is applied to identify groups of countries with similar housing affordability trajectories. The results indicate that macroeconomic factors play a significant role in shaping housing affordability across EU countries. Higher price levels are associated with higher house price-to-income ratios, while income growth partially mitigates affordability pressures. The cluster analysis reveals substantial heterogeneity between European housing markets, highlighting different housing market regimes across EU member states.
Keywords: housing affordability; house price‑to‑income ratio; European Union; housing markets; panel data analysis